1992
DOI: 10.1161/01.str.23.11.1623
|View full text |Cite
|
Sign up to set email alerts
|

Effects in cats of inhibition of nitric oxide synthesis on cerebral vasodilation and endothelium-derived relaxing factor from acetylcholine.

Abstract: Background and Purpose:We investigated the chemical identity of the endothelium-derived relaxing factor generated by acetylcholine in cerebral microvessels by studying the effects and mechanism of action of inhibitors of nitric oxide synthesis from arginine on the vasodilation and endothelium-derived relaxing factor production induced by topical application of acetylcholine in cerebral arterioles.Methods: We determined cerebral arteriolar dilation and endothelium-derived relaxing factor production by bioassay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We found that the vasodilation produced by neocortical application of ACh, a response mediated by local release of endothelial nitric oxide (Faraci, 1992;Wei et al, 1992), is reduced in these mice. The effect cannot be attributed to a nonspecific loss in vascular reactivity or to an impairment of the response of vascular smooth muscles to nitric oxide, because the vasodilation produced by the nitric oxide donor SNAP was not affected.…”
Section: Discussionmentioning
confidence: 78%
“…We found that the vasodilation produced by neocortical application of ACh, a response mediated by local release of endothelial nitric oxide (Faraci, 1992;Wei et al, 1992), is reduced in these mice. The effect cannot be attributed to a nonspecific loss in vascular reactivity or to an impairment of the response of vascular smooth muscles to nitric oxide, because the vasodilation produced by the nitric oxide donor SNAP was not affected.…”
Section: Discussionmentioning
confidence: 78%
“…Vessel diameters were measured 2-4 min following the topical application for each concentration of ACh. Under normal physiological conditions, ACh is known to dilate cerebral vessels via generation of an endotheliumderived relaxing factor of the NO type (Furchgott, 1983;Kontos et al, 1988;Wei et al, 1992). However, this normal vasodilator response caused by ACh is either reduced or converted to vasoconstriction following experimental TBI.…”
Section: Hypercapniamentioning
confidence: 99%
“…There is a precedent for the latter suggestion since indomethacin blocks phospholipase at concentrations that overlap with those on the concentrationinhibition curve for cyclooxygenase. 54 The data showing inhibition of L-NMMA's effects by either cyclooxygenase inhibitors or SOD were not replicated in a study of cat vessels, 52 but in the latter study there was no attempt made to prevent the action of L-NMMA. Instead, SOD was used in an attempt to reverse the effect of L-NMMA after it had br;en present for over an hour.…”
mentioning
confidence: 99%